Interfaces entre os avanços científicos e tecnológicos e as novas competências da área de gestão de pessoas em universidades: o caso da UFSCar - Perseguino, Silvana Aparecida (Universidade Federal de São Carlos, 2011)
With the object of study the management of people in universities, this research presents an analysis of the current process of organizational change in the sector of Personnel Management of a federal public institution of higher education in the face of the National Policy for Staff Development. The objectives were to identify factors that may interfere with the implantation of a new model of management of people in universities, specifically the model based on competencies, contextualizing the role of technology in the process and the profile of professional people management; and to delineate the profile of the professional active in the area through the mapping of competencies, from the standpoint of instrumental and political, according the spectrum of the field study Science, Technology and Society (STS). This is a case study that took place a federal institution of higher education in transition in its model of people management. For this study in order to collect the data some procedures were used, such as: document research, interviews and questionnaires; and content analysis as a benchmark analysis of the findings. The results show an assessment of the role played by the area of People Management, the factors that interfere in the process of organizational change, the professional profile, based on the approach of competencies, and learning strategies used by professionals. In this context of change in the management of people in universities, there is the emergence of a new professional profile in the area, with technology playing a new role integrative of people management subsystems, leading to the possibility of adopting the model of competency management in the medium and long-term. It shows the premises of the STS field study as possible allies in the area of people management in universities, both for the development of skills such as the processes of selection and construction plans for training and professional development.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Gestão de pessoas; Universidades e faculdades; Gestão por competências; Science, technology and society; People management; Universities; Competencies; CIENCIAS SOCIAIS APLICADAS